THU0101 The Incidence of DE Novo Joint Symptoms in A Cohort of IBD Patients during Anti-TNF Treatment. (10th June 2014) - Chimenti, M.S.; Conigliaro, P.; Ascolani, M.; Triggianese, P.; Onali, S.; Ballanti, E.; Collalti, G.; Calabrese, E.; Petruzziello, C.; Pallone, F.; Biancone, L.; Perricone, R.
Abstract : Background: Incidence of de novo joint symptoms in patients with inflammatory bowel disease (IBD) treated with anti-TNF has not been well defined. Objectives: We aimed to evaluate the incidence and characteristics of joint symptoms in a cohort of IBD patients after the beginning of anti-TNF therapy. Methods: We performed a cohort study on the incidence of joint symptoms in IBD patients treated with Infliximab (IFX) or Adalimumab (ADA) from December 2010 to December 2013. Rheumatologic assessment included clinical evaluation (tender and swollen joint count, ASDAS-CRP) and laboratory assays (ESR, CRP, HLA-B27, RF, APCA and ANA). Data are expressed as mean ± SD. Results: IBD patients treated with anti-TNF who attended the combined Gastroenterology-Rheumatology outpatients clinic were 154. Joint pain was complained by 38 IBD patients (24.7%). Patients with Crohn' disease (CD) were 27/38 (71%, age 43.3±13.9 years, disease duration 14.3±10.4 years, treatment duration 18.6±15.4 months). Patients affected by UC were 11/38 (29%, age 41.3±8.4 years, disease duration 15.8±13.5 years, treatment duration 13±14 months). A de novo inflammatory seronegative arthritis occurred in 8 IBD patients (8/154, 5.2%) during anti-TNF: 6 were classified as peripheral spondyloarthritis (SpA) and 2 as axial-SpA. In 2 of these patients psoriasis was also observed. None of these patients had HLAB27 positivity or history of arthralgia/arthritis. The mean time of appearance of inflammatory pain was of 11+9.8 months (range 2-25) after the beginning of anti-TNF therapy. In 4 cases an increase of immunosuppressive treatment was required, in 2 cases anti-TNF was switched to another anti-TNF and in 2 cases anti-TNF treatment was stopped with improvement of inflammatory joint pain. Clinical and laboratory data are summarised in Table 1. The other IBD patients who complained joint pain during the anti-TNF treatment presented the following diagnosis previously unrecognized: 24 SpA (15.6%), 4 osteoarthritis (2.6%) and 2 fibromyalgia (1.3%). Conclusions: Paradoxical adverse effects have been described with all anti-TNF agents (1). In our cohort of IBD patients treated with anti-TNF the 5.2% of cases presented a de novo inflammatory arthritis that required the cessation of anti-TNF or the implementation of the treatment. The mechanisms by which paradoxical events during anti-TNF treatment occur are not understood and they may be related to the neutralization of TNF, the activation of alternative pathways, or the inability to prevent the onset of articular manifestations. This study suggests that IBD patients treated with anti-TNF should be candidate to a rheumatological assessment because of the high incidence of articular involvement that is often underestimated. References: Cleynen I, Vermeire S. Paradoxical inflammation induced by anti-TNF agents in patients with IBD. Nat Rev Gastroenterol Hepatol. 2012 Sep;9(9):496-503. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3625